Journeys West : Jane and Julian Steward and their guides - Kerns, Virginia, 1948- (University of Nebraska Press, 2010)
"Journeys West traces journeys made during seven months of fieldwork in 1935 and 1936 by Julian Steward, a young anthropologist, and his wife, Jane. Virginia Kerns identifies the scores of Native elders whom they met throughout the Western desert, men and women previously known in print only by initials and thus largely invisible as primary sources of Steward's classic ethnography. Besides humanizing Steward's cultural informants - revealing them as distinct - individuals and also as first-generation survivors of an ecological crisis caused by American settlement of their lands - Kerns shows how the elders worked with Steward. Each helped to construct an ethnographic portrait of life in a particular place in the high desert of the Great Basin."--Jacket.